The Johns Hopkins guide to literary theory & criticism - Groden, Michael; Kreiswirth, Martin; Szeman, Imre, 1968- (Baltimore, Md. : Johns Hopkins University Press, 2005)
"The Johns Hopkins Guide to Literary Theory and Criticism has become the indispensable resource for scholars and students of literary theory and discourse. The long-awaited second edition includes 48 new entries and subentries and has been revised throughout, taking account of ten years of rapidly changing scholarship. While concentrating on the explosion of contemporary critical and theoretical works, the Guide presents a comprehensive historical survey of ideas and individuals ranging from Plato and Aristotle to twentieth-century scholars. It includes more than 240 alphabetically arranged entries on critics and theorists, critical schools and movements, and the critical and theoretical innovations of specific countries and historical periods. It also examines developments in other disciplines which have shaped literary theory and criticism. An international, encyclopedic guide to the field's most important figures, schools, and movements, the new edition reflects the state of literary theory and criticism." http://www.loc.gov/catdir/description/jhu051/2004043814.html.
Includes bibliographical references and indexes.
Keywords: Criticism -- Bio-bibliography.; Literature -- History and criticism -- Theory, etc. -- Bio-bibliography.